Novel protocol to establish the myocardial infarction model in rats using a combination of medetomidine-midazolam-butorphanol (MMB) and atipamezole - Farag, Ahmed; Mandour, Ahmed S.; Hamabe, Lina; Yoshida, Tomohiko; Shimada, Kazumi; Tanaka, Ryou (Frontiers in Veterinary Science, 2022)
Background: Myocardial infarction (MI) is one of the most cardiac attacks causing deaths in humans. Previously validated anesthetic agents used in MI model establishment are currently controversial with severe restrictions because of ethical concerns. The combination between medetomidine, midazolam, and butorphanol (MMB) is commonly used in different animal models. The possibility of MMB combination to establish the MI model in rats did not study yet which is difficult because of severe respiratory depression and delayed recovery post-surgery, resulting in significant deaths. Atipamezole is used to counter the cardiopulmonary suppressive effect of MMB. Objectives: The aim of the present study is to establish MI model in rats using a novel anesthetic combination between MMB and Atipamezole. Results: MI was successfully established with the mentioned anesthetic protocol through the LAD ligation technique and confirmed through changes in ECG and echocardiographic parameters after MI. ECG data was improved after atipamezole administration through a significant increase in HR, PR Interval, QRS Interval, and QTc and a significant reduction in RR Interval. Atipamezole enables rats to recover voluntary respiratory movement (VRM), wakefulness, movement, and posture within a very short time after administration. Echocardiographic ally, MI rats showed a significant decrease in the left ventricular wall dimensions, EF, FS, and increased left ventricular diastolic and systolic internal diameter. In addition, induction Time (3.440 ± 1.044), operation time (29.40 ± 3.663), partial recovery time (10.84 ± 3.313), and complete recovery time (12.36 ± 4.847) were relatively short. Moreover, the success rate of the anesthetic protocol was 100%, and all rats were maintained for one month after surgery with a survival rate of 88%. Conclusion: Our protocol produced a more easily anesthetic effect and time-saving procedures with a highly successful rate in MI rats. Subcutaneous injection of Atipamezole efficiently counters the cardiopulmonary side effect of MMB which is necessary for rapid recovery and subsequently enhancing the survival rate during the establishment of the MI model in rats.